Downregulation of human Wnt3 in gastric cancer suppresses cell proliferation and induces apoptosis - Wang, Hai-Sheng (Onco Targets Ther, 2016)
Aberrant activation of Wnt/β-catenin signaling pathways is closely involved in the occurrence and progression of several types of human malignancies. However, as a fundamental component in this cascade, Wnt3 has not been well understood for the expression level and pathogenic mechanism in gastric carcinogenesis. Here, this research was undertaken to elucidate the important role of Wnt3 in gastric cancer. Wnt3 expression in gastric carcinomas and their respective normal tissues was examined by immunoblotting and immunohistochemistry. In all cases, Wnt3 expression was significantly elevated in gastric carcinomas compared with normal tissues. Knocking down Wnt3 in MGC-803 gastric cancer cells by small interfering RNAs transfection led to an obvious decrease in both transcript and protein levels. Silence of Wnt3 expression in gastric cancer cells inhibited the expression of β-catenin and cyclin D1 genes in Wnt/β-catenin pathway, significantly blocked cellular proliferation, delayed cell cycle, suppressed cell invasion and metastasis, accompanied by a higher apoptosis rate. Together, we conclude that upregulation of Wnt3 plays a crucial role in gastric tumorigenesis by inducing proliferation, migration, and invasion and inhibiting apoptosis of cancer cells, and Wnt3 might be a potential target for the treatment of gastric cancer.